2018
DOI: 10.1051/matecconf/201823003016
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of plasticizing surfactants in alkali-activated cement mortars and concretes

Abstract: Functionality of mortar and concrete mixes is regulated by surfactants, which act as plasticizers. The molecular structure of these admixtures can be changed during hydration of alkali-activated cements (AAC). The objective was to determine the chemical nature of plasticizers effective for property modification of mortars and concretes based on AACs with changing content of granulated blast furnace slag from 0 to 100 %. The admixtures without ester links become more effective than polyesters when content of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
(10 reference statements)
2
21
0
2
Order By: Relevance
“…This makes it possible to reduce cement shrinkage deformation due to the falling pressure in capillaries and slowing down rate of moisture evaporation. Since most of surfactants are ineffective in a hydration medium of AAC, principles of their selection were proposed for such cements according to the criteria of variation of plastic strength [13], stability of molecular structure of admixtures having plasticizing [21] and other types of action [22] in a high alkaline medium. In this regard, it has been shown that maximum plasticizing effect is enabled by addition of sodium lignosulfonate [23], sodium gluconate [24], polyatomic alcohols and other acyclic low-and high-molecular compounds [13].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it possible to reduce cement shrinkage deformation due to the falling pressure in capillaries and slowing down rate of moisture evaporation. Since most of surfactants are ineffective in a hydration medium of AAC, principles of their selection were proposed for such cements according to the criteria of variation of plastic strength [13], stability of molecular structure of admixtures having plasticizing [21] and other types of action [22] in a high alkaline medium. In this regard, it has been shown that maximum plasticizing effect is enabled by addition of sodium lignosulfonate [23], sodium gluconate [24], polyatomic alcohols and other acyclic low-and high-molecular compounds [13].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The presented studies [14][15][16][17][18][19][20][21][22][23][24][25] show positive influence of mineral and organic admixtures on reduction of AAC shrinkage, however there is no explanation of the mechanism of their structure formation. This fact limits understanding ways of regulating proper deformations in artificial stone.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Previous studies have shown that the main products from hydration of alkaline-activated cements are the C-S-H gel [21], zeolites [22] and hydrogranates [23]. Such a composition of new structures makes it possible to reliably fix the elements of heavy metals in the structure of a material.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The results from experimental research into the "alkaliactive aggregate" reaction, reported by different authors [4], allow us to formulate the basis of the AAR reaction mechanism: -cement itself [5], admixtures to concrete [6], and the external aggressive environment [7] are the sources of alkalis [8];…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%